Fiscal Consolidation in the Euro Area : How Much Can Structural Reforms Ease the Pain? - Anderson, Derek (IMF Working Papers; Working Paper ;, 2013)
The IMF's Global Integrated Monetary and Fiscal model (GIMF) is used to examine the scope for structural reforms in the euro area to offset the negative impact of fiscal consolidation required to put public debt back on a sustainable path. The results suggest that structural reforms in core countries could quite reasonably be expected to offset the near term negative impact on activity arising from the required fiscal consolidation that uses a plausible mix of instruments to achieve the permanent improvement in the deficit. However, for the periphery, where the required consolidation is roughly twice as large as that required in the core, the results suggest that it would take several years before structural reforms could return the level of output back to its pre-consolidation path.